Adolescent Premarital Sexual Behavior: A Narrative Review of Challenges, and the Vital Role of Comprehensive Sex Education in Promoting Health and Well-being in Islamic Countries - Lamia Abdulgalil Saif Ali Al-amri; Brihastami Sawitri; Haitham T. S. Mohammed; Hebah Hamood Moqbel (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Adolescents, comprising 1.2 billion globally, face unique challenges during the transformative phase of sexual maturation. This review emphasizes the prevalence of premarital sexual behavior among adolescents, with a focus on Southeast Asia, Indonesia, and Arab nations. The vulnerable nature of this age group is underscored, considering the risks of unsafe abortions, unintended pregnancies, and sexually transmitted diseases. Objective: The primary objective is to offer a comprehensive understanding of premarital sexual behavior in adolescents. By synthesizing recent developments and key findings, this review aims to inform specialists and non-specialists, foster societal dialogue, and serve as a resource for scholars and practitioners interested in adolescent sexual health. Methods: Utilizing PubMed and Google Scholar, an extensive literature search spanning 2018 to 2023 focused on keywords such as